IBN KHALDUN’S ECONOMIC THOUGHT - Hakim, Nurman; Kuswanjono, Arqom (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This study examines Ibn Khaldun’s economic thought as articulated in Muqaddimah, emphasizing its relevance as a holistic and multidisciplinary framework for sustainable development. Using a qualitative literature-based approach, the research analyzes Ibn Khaldun’s concept of ‘Ilm al-‘Umran (the Science of Civilization), which explains the rise and decline of societies through the dynamic interaction of moral, social, economic, political, and historical variables. The findings demonstrate that Ibn Khaldun pioneered core principles of classical economics—centuries before Adam Smith—particularly the labor theory of value, surplus generation (al-kesb), division of labor, market equilibrium, and fiscal dynamics resembling the modern Laffer Curve. His development model integrates six interdependent variables: political authority (G), institutional rules or Shariah (S), population (N), wealth (W), development (g), and justice (j), forming a circular and non-static system known as the Circle of Equity. The study highlights justice (al-‘adl) as the central determinant of sustainable development, asserting that injustice (zulm) acts as the primary trigger for civilizational decline. Ibn Khaldun’s framework further introduces a multidimensional poverty model, recognizing poverty as a function of governance, ethics, human resources, and economic growth rather than income alone. This research concludes that Ibn Khaldun’s integrated, non-Eurocentric approach offers a robust theoretical foundation for contemporary development economics, particularly in addressing governance failure, social justice, and long-term sustainability in modern societies.